1988
DOI: 10.1210/endo-123-1-187
|View full text |Cite
|
Sign up to set email alerts
|

In VivoDistribution of Parathyroid Hormone Receptors in Bone: Evidence that a Predominant Osseous Target Cell Is Not the Mature Osteoblast*

Abstract: Previous studies in vitro and in vivo have demonstrated the presence of receptor sites for PTH on cells of the osteoblast phenotype. Nevertheless, it is unclear whether the diverse functions of this hormone in bone can all be attributed to its interaction with a single cell type. In this study, we have used a radioautographic method to examine the competitive binding of 125I-labeled rat PTH-(1-34) to the long bones of rats in vivo. Our studies confirm the presence of competitive binding to mature osteoblasts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
1
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(59 citation statements)
references
References 22 publications
3
54
1
1
Order By: Relevance
“…Our results also show that mRNA for PTH1R is expressed continuously through the lineage from early progenitor to mature osteoblast and that it tends to peak as osteoblasts reach maturity and then declines concomitantly with downregulation of osteoblast-specific messages. These observations are different from studies reporting that the highest number of receptors is on relatively undifferentiated osteoblasts, with relatively few on the terminally differentiated mature osteoblast (Rouleau et al, 1988), but are in agreement with other studies in which PTH1R has been demonstrated to be high in the mature osteoblast population (Bos et al, 1996;Suda et al, 1996), and with earlier in situ studies showing the receptor to be present on osteoblasts and its immediate precursors (Lee et al, 1994;Silve et al, 1982). The fact that we find both molecules expressed already in immature progenitors through to more mature osteoblasts support the idea of a widespread autocrine/paracrine function for these molecules during osteoblast development (Lanske and Kronenberg, 1998;Suda et al, 1996).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results also show that mRNA for PTH1R is expressed continuously through the lineage from early progenitor to mature osteoblast and that it tends to peak as osteoblasts reach maturity and then declines concomitantly with downregulation of osteoblast-specific messages. These observations are different from studies reporting that the highest number of receptors is on relatively undifferentiated osteoblasts, with relatively few on the terminally differentiated mature osteoblast (Rouleau et al, 1988), but are in agreement with other studies in which PTH1R has been demonstrated to be high in the mature osteoblast population (Bos et al, 1996;Suda et al, 1996), and with earlier in situ studies showing the receptor to be present on osteoblasts and its immediate precursors (Lee et al, 1994;Silve et al, 1982). The fact that we find both molecules expressed already in immature progenitors through to more mature osteoblasts support the idea of a widespread autocrine/paracrine function for these molecules during osteoblast development (Lanske and Kronenberg, 1998;Suda et al, 1996).…”
Section: Discussioncontrasting
confidence: 99%
“…The distribution of PTHR coding sequences detected in mouse tibiae by in situ hybridization was essentially identical to that of P2-specific sequences, i.e., in chondrocytes extending from the proliferative zone to the upper region of the hypertrophic zone of the growth plate, and in both preosteoblasts and osteoblasts below the growth plate (Fig 5). This is consistent with our previous reports of in vivo binding of PTH and PTHrP to bone and cartilage cells (15,(45)(46)(47). D3 treatment markedly decreased the expression of the PTHR coding region in both preosteoblasts and osteoblasts.…”
supporting
confidence: 93%
“…At present, osteocalcin is the only known bone-specific protein produced by osteoblasts (11). This protein is reported to appear in a later stage of osteoblast differentiation (2,34,45), presumably in mature osteoblasts, whereas ALP (2, 34, 45), PTH receptors (29), and type I collagen (31, 34, 45) appear even in less differentiated osteoblasts. Although C26 cells have already acquired a low level of the latter characteristics, but they lack osteocalcin synthesis in an unstimulated state.…”
Section: Discussionmentioning
confidence: 99%